HUBUNGAN KECERDASAN NATURALISTIK DENGAN HASIL BELAJAR KOGNITIF SISWA KELAS X PADA MATERI KEANEKARAGAMAN HAYATI DI SMAN 8 PEKANBARU - Asrina, Nursyahbani; Darmawati; Fitra Suzanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Naturalistic intelligence is one of the dimensions of intelligence that contributes to students’ ability to recognize, understand, and care for the natural environment. In biodiversity learning, naturalistic intelligence is presumed to be associated with students’ cognitive learning outcomes because the subject matter is closely related to natural phenomena. This study aimed to determine the relationship between naturalistic intelligence and the cognitive learning outcomes of tenth-grade students on biodiversity material at SMAN 8 Pekanbaru. The study employed a quantitative correlational research design involving 109 tenth-grade students as the sample. Data on naturalistic intelligence were collected using a questionnaire, while cognitive learning outcome data were obtained through a test. Data were analyzed using the Pearson Product-Moment correlation test. The results showed that students’ naturalistic intelligence was categorized as moderate, with an average score of 2.51, while their cognitive learning outcomes were categorized as sufficient, with an average score of 77.83. Correlation analysis revealed a positive and significant relationship between naturalistic intelligence and cognitive learning outcomes in biodiversity learning, with a correlation coefficient of 0.529 (p < 0.05), indicating a moderate level of association. Therefore, higher levels of naturalistic intelligence tend to be accompanied by higher cognitive learning outcomes.